Pola Komunikasi Organisasi Antar Karyawan Di Pt. Kahatex Garment Solokan Jeruk - Syanti Wulan Sari; Yogie Alontari (KOMVERSAL, 2024)
Organizational communication patterns are very important in an organization, in an organization there are also several problems in communicating repeatedly such as continuous misunderstanding and unstructured messages. As an organization, of course, the company needs to create a pleasant and effective atmosphere for employees so that a good environment and cooperation between fellow employees can be created. Leadership in the organization will run well through the role of communication that connects and unites all employees into a mechanism of cooperation that is able to create interactions between leaders and subordinates. This study aims to determine the communication patterns that occur at PT kahatex garment solokan jeruk and what are the supporting and inhibiting factors. The method used in this research is a qualitative research method using a phenomenological approach. The data collection technique used is interview technique with several informants based on purposive sampling technique. The results of this study indicate that the communication patterns that occur at PT Kahatex garment solokan jeruk are star communication patterns (all channels) and Y communication patterns, one of the supporting factors for the creation of communication patterns is good interpersonal relationships or between employees, the inhibiting factor is that the communication delivered is less structured so that the message conveyed by the leader is long received by employees.